A 3-phase 4-leg 4-wire voltage sag compensator based on three dimensional space vector modulation in abc coordinates - Kosol Oranpiroj (2018)
This paper presents a 3-phase 4-leg 4-wire voltage sag compensator based on three dimensional space vector modulation in abc coordinates which can handle a neutral current under voltage sag and nonlinear load conditions. The topology of this hardware consists of a voltage sag detector, a DC/DC converter, a solid state transfer switch, and a 4-leg inverter. The space vector modulation algorithm using abc coordinates is much simpler and more intuitive than in αβγ representation, reducing the complexity of the modulation algorithm and the computational load associated with it. The main advantages of 4-leg inverter topology and the algorithm lie in providing an extended range for the zero sequence voltages and currents. A 3 kVA prototype was implemented on a dsPIC microcontroller to verify its capabilities. © 2013 American Scientific Publishers All rights reserved.